2015
DOI: 10.1097/bot.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Efficacy of Screw and Washer Fixation as a Method for Securing Olecranon Osteotomies Used in the Surgical Management of Intraarticular Distal Humerus Fractures

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 19 publications
(22 reference statements)
5
45
1
2
Order By: Relevance
“…While intramedullary screw fixation is commonly used to fix olecranon osteotomies [13,14] fewer reports have been published on its use for simple (Mayo type I or IIA) olecranon fractures (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…While intramedullary screw fixation is commonly used to fix olecranon osteotomies [13,14] fewer reports have been published on its use for simple (Mayo type I or IIA) olecranon fractures (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Various research groups analyzed the loading characteristics of different osteosyntheses techniques for olecranon osteotomies (10,11,18,19). A stable osteosynthesis seems best achieved by using either a cancellous screw plus tension band wiring or only tension band wiring.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Woods et al compared different fixation methods for olecranon osteotomy after distal humerus fracture and concluded that age, sex and Charlson comorbidity index were related to nonunion and implant removal after olecranon osteotomy. 23 …”
Section: Discussionmentioning
confidence: 99%